Teaching English to Students with ADHD in Inclusive Primary Schools: Teachers’ Strategies and Perspectives - Divo Pratama Pasaribu; Sholihatul Hamidah Daulay (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Inclusive education has become a key approach to ensuring equal educational opportunities for all learners, including those with attention deficit hyperactivity disorder (ADHD). Although numerous studies have examined ADHD within an educational context, research specifically exploring the teaching strategies employed by English teachers in educating pupils with ADHD in English as a Foreign Language (EFL) class within inclusive primary schools remains limited. This study aims to investigate the strategies used by English teachers to support pupils with ADHD and to explore teachers’ perspectives on inclusive English language teaching. Using a qualitative case study design, this research was conducted at an inclusive primary school in North Sumatra, Indonesia, involving an English teacher with direct experience of teaching pupils with ADHD. Data were collected through semi-structured interviews, classroom observations and document analysis, and analysed using thematic analysis. The findings indicate that the teacher implemented various adaptive strategies, including individualised instruction, teacher proximity, visual aids, interactive learning activities, and simplified instruction. Among these strategies, individualised instruction and teacher proximity emerged as the most influential strategies in maintaining student engagement and supporting behaviour management. This study also found that teachers demonstrated a positive and inclusive perspective by integrating empathy, discipline, equality and responsibility into their classroom teaching practices. These findings contribute to the development of inclusive EFL pedagogy by providing practical evidence regarding effective classroom-based strategies to support learners with ADHD at primary level. In conclusion, inclusive and successful EFL teaching requires a flexible, learner-centred approach to learning, supported by professional development and institutional commitment.